Development of a Risk Management Plan for the construction of the Karian – Serpong water conveyance. Issue 2 (March 2021) - Wibowo, E
Abstract: The Karian - Serpong raw water channel construction project is a pipeline construction project to supply drinking. This water channel flows raw water from the Karian Dam in Lebak Banten to the Water Treatment Plant (WTP) located in the Serpong area. This airway project has a higher composition in its implementation, urgently needs management planning, so that the project can run well and be completed, it does not require delays. This study aims to identify risks, analyze the impact and risk response and compile them into a Risk Management Plan as a supporting document in the implementation of the construction of the Karian - Serpong water conveyance. The study was conducted using the method of Literature Study with Meta-Analysis of research that had been done before on similar construction projects. The results of this study found the supply of materials and equipment needed in the pipeline construction project was the dominant factor influencing the time performance in the pipeline development project. Environmental conditions are protests from residents around the project and the condition of busy traffic around the project is also a dominant factor affecting the speed of project implementation. As a risk response in this research is the equipment and materials must be done well before the project runs, during the project must be controlled and ensured always available in the project following with the needs of the project. Communication and coordination with residents around the project must be done well, traffic around the project must also be regulated properly so as not to regulate pipeline construction projects. It is hoped that later this Risk Management Plan can be useful for contractors in managing risks during project implementation and providing input to the Ministry of Public Works and Public Housing for subsequent implementation of similar projects.